The role of grandparents of children with cancer in the hospital - Leticia Bottcher Dias; Ana Márcia Chiaradia Mendes-Castillo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To understand the role of grandparents of hospitalized children with cancer. Methods: In a qualitative study, we interviewed eleven grandparents of children with cancer hospitalized at a referral center for pediatric oncology in São Paulo. The data were analyzed using the Hybrid Framework of Thematic Analysis. Results: Six themes were found to describe the role of grandparents in this context: Being the family's support, Sharing love to my child and my grandchild, Being there for my child and my grandchild, Offering spiritual support to my child and my grandchild, Making an effort to be able to manage my own feelings and Balancing the demands of hospitalization with available resources. Final considerations: The findings show the significance of the grandparents' role in this experience and emphasize the value of being considered, by health professionals, as part of the family and care.